(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2022)
Purpose: Migrations are a complex economic variable that is highly influenced by conditions such as social, societal, economic, political, environmental, and the like. The preferences of the population vary and in accordance with their own needs, the population decides to migrate. Many economies of the world are facing the problem of out-migration of the young population. Moreover, the elderly population is increasing as a percentage of the total population. The aim of this research is to show the gender and age structure of the population, the state of migration and the impact on the economic growth in the Republic of Croatia. Methodology: Data on the population structure and migration in the Republic of Croatia are analyzed for the period 2004-2019. Results: The research conducted suggests that the population of the Republic of Croatia is facing a large outflow of young people and a decline in the birth rate. Conclusion: In the Republic of Croatia, the age structure of the population follows global trends, which means that there is a larger proportion of the elderly population. Such changes have serious consequences for sustainable economic growth for any country, including the Republic of Croatia.